Causes and Management Outcome of Small Intestinal Obstruction in Nekemte Referral Hospital, Nekemte, Ethiopia, 2017 - Tadeg Jemere (Hindawi Limited, 2021)
Background. Small bowel obstruction is a common and dangerous surgical emergency which is associated with high morbidity and mortality if not managed appropriately and timely. Objective. To determine the causes and management outcome of small bowel obstruction in Nekemte Referral Hospital, Nekemte, Ethiopia. Method. Institution-based retrospective cross-sectional study design was used. Three-year data (from January 1, 2014, to December 30, 2016) were collected from July 1 to August 30, 2017. Data were collected from medical records and checked for any inconsistency, coded, and entered into SPSS version 20 for analysis. Descriptive, binary, and multivariate logistic regression analyses were used. On binary logistic regression analysis, variables with p≤0.25 were selected as a candidate for multivariate logistic regression analysis. The level of statistical significance was set at p≤0.05. Results. With 100% response rate, records of 211 patients with small intestinal obstruction were retrieved for analysis. One hundred thirty-seven (64.9%) were males. The commonest cause of small bowel obstruction was adhesion (35.1%). More than a quarter (26.5%) participants developed postoperative complications, and wound infection was the commonest postoperative complication (49.2%). A majority (84.8%) of patients improved and were discharged, and the rest 15.2% of patients died. Sex (AOR = 3.98, 95% CI: 1.51–10.52), duration of illness before surgical intervention (AOR = 4.4, 95% CI: 1.69–11.45), level of hematocrit (AOR = 4.25, 95% CI: 1.56–11.57), types of intestinal obstruction (AOR = 3.73, 95% CI: 1.09–12.64), and length of hospital stay (AOR = 4.69, 95% CI: 1.82–12.07) were independent predictors of the management outcome of patients with small bowl obstruction. Conclusion. Small bowel obstruction is a commonly encountered surgical emergency. Adhesion, small bowel volvulus, and intussusception were the leading causes of small bowel obstruction, respectively.